Effects of coarse aggregate content on the paste rheological thresholds of fresh self-compacting concrete. (30th May 2019) - Zhang, Jingbin; An, Xuehui; Yu, Yuzhen; Nie, Ding
Highlights: A new theoretical model was established for SCC. A coefficient in the plastic viscosity threshold formula was modified. Bilinear interpolation method was used to determine the SCP and SCC zones. Prediction accuracies based on figure area were defined. Proposed method is independent of the type of cement. Abstract: This work studies the effects of coarse aggregate content on the paste rheological thresholds of fresh self-compacting concrete (SCC). A new mechanical model for highly flowable SCC was established, and a coefficient in the plastic viscosity threshold formula was modified after conducting experimental tests on Wu's model. The threshold of the paste yield stress decreases while the threshold of the paste plastic viscosity increases with the increase of aggregate content. The bilinear interpolation method was used to process the paste and SCC results. Prediction accuracy formulae based on figure area were introduced to assess the predictive effect of the new model. The relative accuracies of the new model are greater than 70%, whereas the relative accuracies of Wu's model are no greater than 45%. At last, Two types of cement were used to conduct the verification experiments and high prediction accuracies were obtained. The results show that the application of this method is independent of the type of cement used.